Pengaruh Kualitas Auditor Terhadap Pengungkapan Related Party Transaction (RPT): Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI - Ayunni, Zahara Delfi; Cheisviyanny, Charoline (Universitas Negeri Padang, 2025)
This study aims to examine the influence of Big 4 Auditors and Industrial Specialization Auditors on the disclosure of Related Party Transactions in manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2022. The sample selection technique in this study used purposive sampling so that a sample of 209 companies was obtained for research. Disclosure of Related Party Transactions is the dependent variable in this research using measurements adopted from Feleaga & Neacsu (2016) and Big 4 Auditors and Industrial Specialization Auditors are independent variables measured by dummy variables. The results of this research found that Big 4 Auditors and Industrial Specialization Auditors had a positive and significant effect on the disclosure of Related Party transactions.